Carotid blowout—a rare but fatal complication of endoscopic submucosal dissection of superficial hypopharyngeal carcinoma after radiotherapy. Issue 1 (February 2022) - Okabe, Ryuichi; Ueki, Yushi; Takahashi, Takeshi; Shodo, Ryusuke; Yamazaki, Keisuke; Hashimoto, Satoru; Horii, Arata
Abstract: Endoscopic submucosal dissection (ESD) has gained wide acceptance as a minimally invasive and curative surgery for superficial head and neck carcinoma. However, the safety of ESD for superficial pharyngeal carcinoma after radiotherapy has not been elucidated. Superficial hypopharyngeal carcinoma of the left pyriform sinus developed in a 76-year-old man who had undergone concurrent chemoradiotherapy for T2N2bM0 pyriform sinus carcinoma on the opposite side 12 months before. He underwent ESD without complications. Because tumor invasion into the muscular layer was a concern, the muscular layer was partially resected with the tumor. Twelve days after discharge, he presented with a sore throat and difficulty in swallowing. Endoscopy and computed tomography revealed necrosis due to wound infection with abscess formation around the left carotid artery. The common carotid artery subsequently ruptured. Although the surgical intervention was performed, he passed away 46 days after ESD due to carotid blowout. ESD is a minimally invasive treatment for superficial head and neck carcinoma, but carotid blowout can occur in cases after radiation. Prior radiotherapy and deeper dissection into the muscular layer may hamper wound epithelization, resulting in infection-induced necrosis and carotid blowout. Diligent monitoring of wound healing is essential in patients who have previously undergone irradiation.